The Influence of Ease of Use and User Trust on Mobile Payment: Social Influence as a Moderating Variable - Agustiningtyas, Wahyu Eka Putri; Nasir, M Jamal Abdul; Arumsari, Yuni Kusuma (Fakultas Ekonomi Universitas Kadiri, 2025)
This study examines the impact of usability and user trust on intention to use mobile payments among Generation Z, with social influence as moderating. This study used a quantitative approach, as the method of data collected was survey and moderated regression analysis. The research showed findings that usability and user trust, have a favorable impact on the intention to use mobile payment methods. Furthermore, social influence strengthens this relationship, indicating that social support plays an important role in Generation Z's decision to use mobile payments. These findings underscore the importance of developing more user-friendly systems and community-focused marketing strategies